PsycEXTRA Dataset 2011
DOI: 10.1037/e520602012-288
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Format Physical Similarity Effects and Their Implications for the Numerical Cognition Architecture

Abstract: The sound |faIv| is visually depicted as a written number word "five" and as an Arabic digit "5." Here, we present four experiments -two quantity same/different experiments and two magnitude comparison experiments -that assess whether auditory number words (|faIv|), written number words ("five"), and Arabic digits ("5") directly activate one another and/or their associated quantity. The quantity same/different experiments reveal that the auditory number words, written number words, and Arabic digits directly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Second, we would examine the possible mechanism among the relationship of physical similarity, numerical distance, and participants’ performance. In the study by Cohen et al (2013), the physical similarity was found to be another significant predictor of participants’ performance in addition to the numerical distance in the numerical comparison task; however, it is not clear whether the effect of physical similarity on participants’ performance is mediated by the numerical distance. This question is examined in our study.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Second, we would examine the possible mechanism among the relationship of physical similarity, numerical distance, and participants’ performance. In the study by Cohen et al (2013), the physical similarity was found to be another significant predictor of participants’ performance in addition to the numerical distance in the numerical comparison task; however, it is not clear whether the effect of physical similarity on participants’ performance is mediated by the numerical distance. This question is examined in our study.…”
Section: Introductionmentioning
confidence: 92%
“…This effect seems to be the primary factor controlling participants’ performance. However, in recent years several studies have identified an alternative perceptual factor to explain participants’ performance (e.g., Cohen, 2009; Cohen, Warren, & Blanc-Goldhammer, 2013; Defever et al, 2012; Garcia-Orza et al, 2012; Wong & Szűcs, 2013). In the seminal study by Cohen (2009), participants were presented with a single Arabic number between 1 and 9 and were asked to decide whether the number presented was 5 or not 5.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations